Strategy for Developing Internal Quality Assurance of Schools Under Khon Kaen Primary Educational Service Area Office 1 - Artwichian, Khanitta; Rooyuenyong, Wichian (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) study the current condition, desired condition, and needs of internal quality assurance in schools under Khon Kaen Primary Educational Service Area Office 1, and 2) propose strategies for developing internal quality assurance in schools und erKhon Kaen Primary Educational Service Area Office 1, using mixed methods research. In Phase 1, the population consisted of 1,531 school administrators and teachers, and 317 samples were taken using the Taro Yamane formula at a sampling error level of .05, using stratified random sampling and simple random sampling. In Phase 2, the target group consisted of 3 experts. The research instruments consisted of a 5-level rating scale questionnaire with a consistency index of 0.66-1.00, a reliability of 0.93, and a semi-structured interview. The statistics used for data analysis included frequency, mean, standard deviation, and Priority Needs Index (PNIModified). The research found that 1. The current condition of internal quality assurance of schools under Khon Kaen Primary Educational Service Area Office 1, both overall and in each aspect, is at a moderate level. The desired condition is at a high level. Urgent needs, ranked from most to least, are Standard 3: Development of the quality of learning management, Standard 2: Development of the quality of school management, and Standard 1: Quality of learners, respectively. 2. The strategy for developing internal quality assurance of schools under Khon Kaen Primary Educational Service Area Office 1 consists of 3 strategies: Strategy 1) Raise the quality of teaching management that focuses on learners; Strategy 2) Accelerate the development of the quality of school management to be effective; Strategy 3) Develop learners to have quality according to the standards.